2011
DOI: 10.1021/nn202144b
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Polymer Tandem Solar Cell

Abstract: We demonstrated plasmonic effects in an inverted tandem polymer solar cell configuration by blending Au nanoparticles (NPs) into the interconnecting layer (ICL) that connects two subcells. Experimental results showed this plasmonic enhanced ICL improves both the top and bottom subcells' efficiency simultaneously by enhancing optical absorption. The presence of Au NPs did not cause electrical characteristics to degrade within the tandem cell. As a result, a 20% improvement of power conversion efficiency has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
260
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(263 citation statements)
references
References 40 publications
0
260
1
2
Order By: Relevance
“…4 Kulkarni et al 4 showed that charge carrier generation could be enhanced more than 3 times if a thin film of silver nanoprisms was introduced under the organic photovoltaic materials, which could in principle be used to increase photocurrent in organic thin film solar cells. By blending Au nanoparticles with poly(3,4-ethylenedioxythiophene)-poly-(styrenesulfonate) (PEDOT:PSS), Yang et al 10 showed that plasmonic optical absorption can be used to enhance the photovoltaic performance of tandem structured organic solar cells. However, early studies have not shown the improved energy conversion efficiency in organic solar cells when plasmonic metal nanostructures were embedded into the photoactive layer, although plasmon resonant enhanced optical absorption existed; this is due to the reduced hole mobility caused by disturbed ordering in the polymer phase, or the quenching of excited states in the photoactive polymers.…”
mentioning
confidence: 99%
“…4 Kulkarni et al 4 showed that charge carrier generation could be enhanced more than 3 times if a thin film of silver nanoprisms was introduced under the organic photovoltaic materials, which could in principle be used to increase photocurrent in organic thin film solar cells. By blending Au nanoparticles with poly(3,4-ethylenedioxythiophene)-poly-(styrenesulfonate) (PEDOT:PSS), Yang et al 10 showed that plasmonic optical absorption can be used to enhance the photovoltaic performance of tandem structured organic solar cells. However, early studies have not shown the improved energy conversion efficiency in organic solar cells when plasmonic metal nanostructures were embedded into the photoactive layer, although plasmon resonant enhanced optical absorption existed; this is due to the reduced hole mobility caused by disturbed ordering in the polymer phase, or the quenching of excited states in the photoactive polymers.…”
mentioning
confidence: 99%
“…"If we can turn half the windows in New York City into solar cells with 5-10% efficiency, I think we can really do something for the solar industry, " Yang says. He estimates that in some locations, solar cells applied to the windows of one 30-storey building could provide enough electricity to meet the needs of 25 households 1 .…”
Section: Trick Of the Lightmentioning
confidence: 99%
“…В связи с этим исследование влияния поверхностного плазмонно-го резонанса (ППР) на параметры полимерных и композитных СЭ на основе поли(3-гексилтиофена) (Р3НТ) и производных фуллеренов ([60]РСВМ) получили в последние годы значительное развитие [1][2][3][4][5]. В частности, было показано, что введение наночастиц золота (Au) [1][2][3], серебра (Ag) [1,4], меди (Cu) [5] в тонкие пленки Р3НТ : [60]РСВМ приводит к росту поглощения в видимой области спектра в таких системах за счет возбуждения поверхностного плазмона на его ре-зонансной частоте внешней электромагнитной волной, что увеличи-вает эффективность СЭ.…”
unclassified